Overview of the Appearance of Management Information Systems In Hungarian Higher Education through the Example of the University of Debrecen - Vincze, Szilvia; Gebei, Tímea (International Journal of Engineering and Management Sciences, 2019)
In recent years, the ever-decreasing number of students in Hungarian higher education has created a serious competition between institutions, in which not only national but also foreign universities prove to be competitive. In order for national institutions to be able to compete adequately in this competition, managers need to be provided with well-structured, up-to-date information that can support decision-making. The management information system, which successfully adapted at the University of Debrecen, has been in operation for years and provides significant support in data reporting and ad hoc reporting, but there are still many opportunities for advancement. The study draws attention to the importance of management information systems through the example of the University of Debrecen.